Student Cognitive Performance Level Based on SOLO Taxonomy and Student’s Personality Type - Hidayanti, Alfi Nur; Sulaiman, Raden; Ekawati, Rooselyna (Jurnal Riset Pendidikan dan Inovasi Pembelajaran Matematika, 2024)
This research study aims to analyze the level of cognitive performance of students basedon the SOLO Taxonomy in solving mathematics story problems in terms of student’spersonality type. This study uses descriptive qualitative method. The data analysistechnique used is data reduction, data presentation, and conclusions. There are 5 subjectsin this study, which is taken from seventh grade junior high school students using purposivesampling technique based on the results of personality type questionnaires. From theresults, in one class the dominant personality type is the Extraversion personality, followedby Conscientiousness, Openness, Agreeableness, and Neuroticism. Based on analysis resultand the fulfillment of SOLO Taxonomy indicators, students with Openness andAgreeableness personality types can reach multi-structural level with cognitiveperformance level being able to use some relevant information to solve problems.Conscientiousness type students are able to reach rational level with cognitive performancelevel who can use some relevant information and its relationship to solve problems.Extraversion students are able to achieve Extended Abstract level with the level ofcognitive performance who can relate some relevant information and generalize it to solveproblems. Neurotism students are able to reach uni-structural level by only being able tofocus on one relevant information and have difficulty to determine problem solvingstrategies. Therefore, it is obtained that the personality type possessed by studentscontribute to the level of student’s cognitive performance which can be seen from the waystudents make decisions when working on the given math story problems